An Extra-Qualitative Alternative to the Qualitative Interpretation of Absolute Individuation. - Liu, Zixuan (Husserl Studies, 2025)
Husserl's thesis of absolute individuation consists of two ideas: (1) unlike experiences and mundane entities, which are individuated via spatiotemporal position, the subject has its own principle of individuation and (2) even for non-subjects, the ultimate principle of individuation is their relationship with the subject. Absolute individuation is sometimes qualitatively interpreted (even by Husserl): owing to habituation, a subject's personal character cannot be reinstantiated elsewhere. I argue against the qualitative interpretation for two reasons. The first is its inconsistency with Husserl's account of the individuation of non-subjects. Maximally specific universals cannot individuate a non-subject because they can be multiply instantiated, at least in different phantasies. If multiple instantiation is also possible for personal characters, then this poses a problem for the qualitative interpretation. The second reason is that the qualitative interpretation cannot explain the subjective contribution to the individuation of non-subjects. I consequently propose an extra-qualitative interpretation: The relevant subject should be defined as one-off sic et simpliciter. It has no other determinations than one-offness and is, thus, pre-spatiotemporal. This can explain what individuates instances of maximally specific spatiotemporal universals, thereby addressing (2) above. It also highlights the need to recognize the respective contributions made by multiple notions of the subject. Husserl's context-dependent distinction between constitutive determinations and principia individuationis may shed light on the qualitative/non-qualitative difference in contemporary metaphysics. The hierarchical model of individuation can also illuminate the debate around possible worlds and haecceitism.